Cover, Content, and Editorial Note from Borneo J Pharm Vol. 7 No. 3 August 2024 - Borneo J Pharm, Chief Editor of (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published at August 2024. This edition contains ten articles: Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Analytical Pharmacy-Medicinal Chemistry, Microbiology Pharmacy, Natural Product Development, Clinical-Community Pharmacy, and Pharmaceutical Education. This edition includes writings from four countries: India, Indonesia, Italy, and Malaysia. The authors come from several institutions, including Universitas Muhammadiyah Malang, Universitas Ahmad Dahlan, Universitas Muhammadiyah Banjarmasin, Universitas Jember, Università degli Studi del Piemonte Orientale “Amedeo Avogadro”, University of Kalyani, Azienda Ospedaliero Universitaria Maggiore della Carita, Universitas Airlangga, Institut Ilmu Kesehatan Bhakti Wiyata Kediri, Universitas Islam Bandung, Universitas Mulawarman, Universitas Negeri Yogyakarta, Universitas Gadjah Mada, Universitas Kristen Duta Wacana, Universitas Global Jakarta, and Management and Science University. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors, could re-participate for the publication in the next edition on November 2024. Wassalamu’alaikum Wr. Wb.